2022
DOI: 10.3389/fimmu.2022.1080822
|View full text |Cite
|
Sign up to set email alerts
|

Defective antifungal immunity in patients with COVID-19

Abstract: The COVID-19 pandemic has placed a huge strain on global healthcare and been a significant cause of increased morbidity and mortality, particularly in at-risk populations. This disease attacks the respiratory systems and causes significant immune dysregulation in affected patients creating a perfect opportunity for the development of invasive fungal disease (IFD). COVID-19 infection can instill a significant, poorly regulated pro-inflammatory response. Clinically induced immunosuppression or pro-inflammatory d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…Immune system dysregulation is manifested through the functional debilitation of natural killer cells and T cells. This has been detected in COVID-19 patients through decreased levels of its markers, NK-G2A and PD-1 [12] . Reduced fungicidal activity of neutrophils from COVID-19 patients indicates that immune imbalance is an important risk factor for invasive fungal diseases.…”
Section: Discussionmentioning
confidence: 94%
“…Immune system dysregulation is manifested through the functional debilitation of natural killer cells and T cells. This has been detected in COVID-19 patients through decreased levels of its markers, NK-G2A and PD-1 [12] . Reduced fungicidal activity of neutrophils from COVID-19 patients indicates that immune imbalance is an important risk factor for invasive fungal diseases.…”
Section: Discussionmentioning
confidence: 94%
“…Thus opportunistic Candida infection due to immune hypo reaction may be more common in adults. In addition, other authors have reported that several pathogenic mechanisms occurring during COVID-19, such as immunosuppression and pro-inflammatory cytokines cascade, associated with the reduced fungicidal activity of neutrophils may cause direct damage to the oral mucosa and contribute to streamlining the Candida infections [ 36 ].…”
Section: Possible Mechanisms Underlying Oral Candidiasis In Adult And...mentioning
confidence: 99%
“…Most cases of Candida infection in COVID-19 patients occur in subjects admitted at the intensive care units (ICUs), meanly after a week from the recovery [ 50 , 51 ], being responsible for a two-fold mortality risk compared to patients with candidemia without COVID-19 [ 36 , 50 , 52 ].…”
Section: Possible Mechanisms Underlying Oral Candidiasis In Adult And...mentioning
confidence: 99%
“…Patients hospitalized with COVID-19 receive immunosuppressive medication that potentially increases the susceptibility of these patients to co-infections, including polymicrobial Candida infections [ 21 , 22 ]. However, according to the literature, this is not the only reason for the increase in invasive fungal infections [ 23 ]. Defective antifungal immunity in patients of COVID-19 due to a dysregulation of the immune system has been observed through the expression of exhaustion markers of natural killer cells and T cells [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, according to the literature, this is not the only reason for the increase in invasive fungal infections [ 23 ]. Defective antifungal immunity in patients of COVID-19 due to a dysregulation of the immune system has been observed through the expression of exhaustion markers of natural killer cells and T cells [ 23 ]. In addition, patients with COVID-19 also have reduced fungicidal activity of neutrophils [ 23 ].…”
Section: Introductionmentioning
confidence: 99%